Development of an accurate DWIA model of coherent π0 —photoproduction to study neutron skins in medium heavy nuclei. (December 2020) - Colomer, F.; Capel, P.; Ferretti, M.; Thiel, M.; Sfienti, C.; Tsaran, V.; Vanderhaeghen, M.
Abstract: Despite decades of studies which have seen the nuclear charge distribution being measured with increasing precision, the neutron distribution remains elusive. The difference between the neutron and proton distributions is often expressed as the difference of their root mean square radii: the neutron skin thickness. Recently, the A2 collaboration at MaMi has measured the skin thickness in lead through coherent pion photoproduction [1] with a very high precision. However, they do not include theoretical uncertainties, which can be significant for this process. A new reaction code in the distorted wave impulse approximation (DWIA) is developed to help the (ongoing) analysis of the recent measurement by the A2 collaboration at MaMi of the coherent pion photoproduction cross section on 116, 120, 124 Sn isotopes [2] and to properly quantify the theoretical uncertainties.